Implementation of Unit Dose Dispensing using Management Information System in Pharmacy Installation of Panti Rapih Hospital - Niken Larasati; Christina Asri Wulandadari (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Unit Dose Dispensing (UDD) is a drug distribution system in hospitals, where drugs are packaged in the form of a single dose and submitted to patients for one use during treatment. One of the hospitals that has applied UDD with information system utilization is Panti Rapih Hospital. The purpose of this study is to evaluate the application of UDD using Management Information System (SIM RS) with the Technology Acceptance Model (TAM) method. This research used descriptive quantitative analytic to present facts systematically. This method is also used to understand and conclude the facts more easily. Hypothesis testing was conducted to see the relationship and influence between variables. This test was conducted using Partial Least Square (PLS) analysis. The hypothesis testing applied was two-way probability with a significant level (α) of 5%. When the p-value of less than 0,05, the data is significant. In addition, the relationship between variables is seen from the original sample value. The result shows the relationship of perceived ease of use to perceived usefulness, the relationship of perceived usefulness to attitude toward using, and the relationship of perceived usefulness to behavioral intention to use has a negative and insignificant effect. On the other hand, the relationship of perceived ease of use to the attitude toward using, the relationship of attitude toward using to the behavioral intention to use, and the relationship of behavioral intention to use towards actual system usage conditions have a positive and significant effect on implementation of UDD using the SIM RS in Pharmacy Installation Panti Rapih Hospital.